New Vistas in Halogen/Metal Exchange Reactions: The Discrimination Between Seemingly Equal Halogens - Leroux, Frederic; Nicod, Nathalie; Bonnafoux, Laurence; Quissac, Berengere; Colobert, Francoise (Letters in Organic Chemistry, 2006)
Regioselective halogen/lithium permutation reactions were carried out on polybrominated biaryls. Thus, highly functionalized, dissymetrically substituted biaryls become easily accessible on gram scale.
Keywords: polar organometallic methods